Performance of modified sampling technique in reducing disturbance on peat soil sample - Cecelia, Linggang (2016)
Peat soil was known as one of the most problematic soil in the construction industry. It has excessive moisture content, with high compressibility making it unsuitable for any type of foundation. In order to deal with the current urban land scarcity for development, geotechnical engineers have been challenged to design foundations in marginalized soil including peat. Hence a good sampling technique was necessary to accurately estimate soil properties and the strength to design suitable foundations on peat. The main objective of this study is to measure the performance of modified peat sampler in reducing disturbances on peat soil during sampling work. There are two types of sampler used to obtain the undisturbed peat soil sample which was Tropiter and conventional tube sampler. Peat soil sample was obtained from Pekan, Pahang at the depth of 300 mm using conventional as well as the modified sampler for comparison. The degree of disturbance in Tropiter (23%) was less than the conventional tube sampler (37.33%). Laboratory tests conducted on samples obtained from these samplers were compared with the existing field data from literature. Based on the result obtained, the sample was classified as H3 which is sapric peat with 33.24% organic content and 30.54% of fiber content. The moisture content is 362.12%. The specific gravity and unit weight is 1.91 and 12.82